ЛИМОНДЫ КӨБЕЙТИЎ УСЫЛЛАРЫ - Балтабаев, М.Т.; Ражабова, С.К. (SCIENCE and SOCIETY, 2016)
Lemon is grown by seeds, cuttings and vaccinations. Propagated lemon seeds bear fruit later. In most cases, lemon is propagated by grafting, but in this case the plant develops slowly. The best way to grow a lemon is by cuttings.